2021
DOI: 10.1063/5.0046933
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layer Gaussian-based multi-configuration time-dependent Hartree (ML-GMCTDH) simulations of ultrafast charge separation in a donor–acceptor complex

Abstract: We report on first applications of the Multi-Layer Gaussian-based Multi-Configuration Time-Dependent Hartree (ML-GMCTDH) method [Römer et al., J. Chem. Phys. 138, 064106 (2013)], beyond its basic two-layer variant. The ML-GMCTDH scheme provides an embedding of a variationally evolving Gaussian wavepacket basis into a hierarchical tensor representation of the wavefunction. A first principles parametrized model Hamiltonian for ultrafast non-adiabatic dynamics in an oligothiophene-fullerene charge transfer comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Returning to the original MCTDH ansatz, instead of replacing the SPFs by GWPs, it is more fruitful to consider the GWPs as a time-dependent primitive basis set and expand the SPFs in terms of these [6]. This leads naturally to a multi-layer version able to treat many degrees of freedom [29,30]. In the present work, however, we will stick to the single layer ansatz equation (2.3) and expand the SPFs…”
Section: (B) the Variational Multi-configurational Gaussian Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Returning to the original MCTDH ansatz, instead of replacing the SPFs by GWPs, it is more fruitful to consider the GWPs as a time-dependent primitive basis set and expand the SPFs in terms of these [6]. This leads naturally to a multi-layer version able to treat many degrees of freedom [29,30]. In the present work, however, we will stick to the single layer ansatz equation (2.3) and expand the SPFs…”
Section: (B) the Variational Multi-configurational Gaussian Methodsmentioning
confidence: 99%
“…Returning to the original MCTDH ansatz, instead of replacing the SPFs by GWPs, it is more fruitful to consider the GWPs as a time-dependent primitive basis set and expand the SPFs in terms of these [6]. This leads naturally to a multi-layer version able to treat many degrees of freedom [29,30]. In the present work, however, we will stick to the single layer ansatz equation (2.3) and expand the SPFs φjfalse(κfalse)false(Qκfalse)=k=1Nκdakjfalse(κfalse)false(tfalse)gkfalse(κfalse)false(Qκ,tfalse). If the GWPs are frozen and separable, it can be easily shown that this approach still uses a superposition of GWPs for the wave function ansatz right left right left right left right left right left right left3pt0em 2em 0em 2em 0em 2em 0em 2em 0em 2em 0emtrueΨ(boldq,t) =j1=1n1jp=1npAj1jf(t)κ=1p(kκ=1Nκdakκjκfalse(κfalse)false(tfalse)gk…”
Section: Background Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Using the multi-layer variant of MCTDH (ML-MCTDH), they could treat seven excited states and all 49 vibrational degrees of freedom and assess the accuracy of the different models. Di Maiolo et al 41 again use the ML-MCTDH method and study an even larger system. Using a parameterized vibronic coupling model, the photo-initiated charge transfer in a fullerene-oligothiophene complex with up to 300 vibrational modes is studied.…”
Section: Editorial Scitationorg/journal/jcpmentioning
confidence: 99%
“…From magnetic materials to molecular aggregates, a vast variety of interesting physical phenomena lend themselves to be modeled as extended one-dimensional quantum systems interacting with open thermal environments. Wave functionbased methods such as density matrix renormalization group [1][2][3][4][5][6] (DMRG) and multi-configuration time-dependent Hartree [7][8][9] (MCTDH and ML-MCTDH) and related methods have proven to be exceptionally useful in simulating the quantum dynamics of extended systems. However, due to their computational complexity, these methods are typically less useful when it comes to simulations of open systems.…”
mentioning
confidence: 99%